PELAKSANAAN WORKSHOP DI SMP NEGERI 6 MEDAN UNTUK MENINGKATKAN KUALITAS KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN (RPP) DAN SILABUS TAHUN PEMBELAJARAN 2019/2020 - Arifuddin Arifuddin (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2021)
The purpose of this school action research (PTS) is to increase the level of understanding of teachers, especially at SMP Negeri 6 Medan in compiling and developing the syllabus and lesson plans (RPP) through workshops. The method used in this study is the School Action Research (PTS) method. The subjects of this study were teachers of SMP Negeri 6 Medan from various subjects as many as 48 people. Data collection techniques used are in the form of observation sheets, interviews and documentation studies. Based on the results of the assessment through the Syllabus and Learning Implementation Plan (RPP) assessment format in the second cycle, which reached a score of 86.7, it was in the very good category. The competence of SMP Negeri 6 Medan teachers in compiling, developing, perfecting the syllabus and lesson plans in orientation activities or before taking corrective actions in the second cycle is very limited